202k views
3 votes
Solve by factoring...

1) y=6x^2-13x-5

2) y=4x^2-7x+3

1 Answer

5 votes

Answer:

1)
x=-(1)/(3), x=(5)/(2)

2)
x=1, x=(3)/(4)

Explanation:

1)

Given


f(y)= 6x^(2) -13x-5=0

Equating above equation.


6x^(2) +2x-15-5=0


2x(3x+1)-5(3x+1)=0


(3x+1)(2x-5)=0

Solving for both the equation


3x+1=0


3x=-1


x=-(1)/(3)


2x-5=0


2x=5


x=(5)/(2)


x=-(1)/(3) ,x=(5)/(2)

2)

Given


f(y)=4x^(2) -7x+3=0


4x^(2) -4x-3x+3=0


4x(x-1)-3(x-1)=0


(x-1)(4x-3)=0

Solving for both equation


x-1=0


x=1


4x-3=0


4x=3


x=(3)/(4)


x=1, x=(3)/(4)

User Warpdesign
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.